The challenges, methods and results of teaching GB pronunciation to Slovene EFL students - Komar, Smiljana (ELOPE (Ljubljana), 2019)
The paper presents and discusses the results of a study whose main purpose was to test the oral production of General British (GB) sounds in connected speech by Slovene BA students of English. Previous studies in contrastive English-Slovene pronunciation were mainly concerned with the perception and production of individual sounds. Our study, on the other hand, focused on the production of GB sounds in connected speech. We were interested in the state of affairs of English pronunciation before and after a 60-hour intensive and systematic theoretical and practical instruction of English pronunciation. The results confirmed out initial two hypotheses that the influences of L1 phonological and phonetic system, orthography and General American pronunciation were stronger before the instruction, and that the phonemic transcription has a very positive influence on the acquisition of foreign sounds in EFL students.
Keywords: angleško-slovenska analiza napak izgovarjave; fonemska transkripcija; poučevanje angleške fonetike in fonologije; učenje tujih jezikov